2022
DOI: 10.3390/horticulturae8090838
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Characterization of Prunus serotina subsp. capuli

Abstract: Prunus serotina is divided into five subspecies. Among these, P. serotina subsp. capuli, commonly known as capuli, is native to Central and South America. Its fruits are big, sweet, and consumed by locals in various forms, with the Ecuadorian Andes region providing the best fruit forms of capuli. The objective of this study was to characterize a collection of different genotypes of capuli’s fruit, and their endocarps, found growing in the wild in the Chimborazo, Tungurahua, and Cotopaxi provinces of Ecuador. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Due to the diversity of ES identified by locals in the three study areas of the CO, CH, and TU provinces, there are opportunities to conserve specific sites in the central Andes of Ecuador in order to optimize the supply of ES for provisioning, regulating, supporting, and, above all, cultural services which focus on a cultural re-evaluation. This is because Prunus serotina plays an important role in the life of Ecuadorian people [81].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diversity of ES identified by locals in the three study areas of the CO, CH, and TU provinces, there are opportunities to conserve specific sites in the central Andes of Ecuador in order to optimize the supply of ES for provisioning, regulating, supporting, and, above all, cultural services which focus on a cultural re-evaluation. This is because Prunus serotina plays an important role in the life of Ecuadorian people [81].…”
Section: Discussionmentioning
confidence: 99%
“…However, their MI values are significantly higher, with Tianbao at 38.56 ± 1.82 and Qinzhou at 35.22 ± 0.30, which can be attributed to their lower titratable acidity. A series of studies confirmed that the SSC and TA of cherries mainly depend on cultivars [58,59]. Therefore, it can be seen that taking SSC, TA, and MI into account is more comprehensive and reasonable than only detecting the SSC of cherries to measure the fruit's degree of ripening.…”
Section: Variability In Physicochemical Properties Of Gi Cherriesmentioning
confidence: 93%
“…Die Frucht schmeckt süß, manchmal mit einem bitteren und leicht säuerlichen Nachgeschmack. In der Frucht befindet sich ein einzelner, ovaler Samen 4 7 8 9 .…”
Section: Botanische Charakteristikunclassified